The Logic of Impossible Scenarios in Hurtado de Mendoza’s Tractatus de Trinitate - Hanke, Miroslav (Vivarium, 2021)
Abstract Since the late thirteenth century, the counterfactual Filioque debate, i.e., the question whether the Son and the Holy Spirit were distinct persons in the Trinity if the Holy Spirit only proceeded from the Father and not also from the Son, was an interesting context for developing the methodology of extreme thought experiments and the logic of conditionals with impossible antecedents and paradoxes of implication. In the mid-1620s, Puente Hurtado de Mendoza (1578–1641) introduced a strongly critical approach towards the scientific merits of positing certain types of impossible scenarios while joining this traditional debate in his Tractatus de Trinitate. He argued that the counterfactual Filioque problem is (at best) a needless detour and (at worst) either shifts to unreliable discussions of properties of fictional entities or is outright trivial for logical reasons. The present article offers a modern edition of the ninth disputation of Hurtado’s Tractatus de Trinitate and analyses logical and methodological aspects of Hurtado’s position in the counterfactual Filioque debate.